Cuidando da saúde: diálogos sobre a política de atenção integral para a população LGBT - Silva, Marcos Pereira da (2018)
The aim of this research is to understand the meanings built by the community health agents of Belo Horizonte-MG on access and quality of comprehensive health care for the lesbian, gay, bisexual, transvestite and transgender (LGBT) population in the Family Health Strategy of the Unified Health System (SUS). Twenty community health agents were interviewed in Belo Horizonte. All the agents were invited to participate freely in the research and, after acceptance, signed the free and informed consent form. The semistructured interview was the instrument used to collect data that, after being recorded, was transcribed and then later updated. The results pointed to the construction of 04 categories that were analyzed from the perspective of Social Constructionism. They constituted the categories of this work: "An epidemic that demarcates places"; "Equality that stifles equity", "Challenges of (in) visibility: delegitimization covered with care and bond" and "Equality that (des) informs services: between demands imagined and denied." In the first category it was possible to perceive that there is a relation between the LGBT population and the Sexually Transmissible Infections and the presupposition of "risk behavior". In the second, a sense of equality prevails that precludes equity in care, and silences the specificities of this population. In the third, the impossibility of recognizing this population is highlighted, through gossip and the supposed linkage with the families and neighbors of LGBT people. In the fourth category, the belief in the competence to care for people who are part of the LGBT population because their actions are anchored in the conception of equality. From the research it is possible to conclude that the speeches of the Community Agents reinforce and create practices that silence the needs and delegitimize the specificities in the health care of the LGBT population, nevertheless, one perceives the availability of them to take care of. It is necessary to build social and political strategies and aim to broaden the debate on these issues and the training of Community Health Agents of the Family Health Strategy.